RvD1 Attenuated Susceptibility to Ischemic AKI in Diabetes by Downregulating Nuclear Factor-κ B Signal and Inhibiting Apoptosis - Li, Zheng; Liu, Zhiwen; Lu, Hengcheng; Dai, Wenni; Chen, Junxiang; He, Liyu (Frontiers in Physiology, 2021)
Background Acute kidney injury (AKI), when occurring in diabetic kidney disease (DKD), is known to be more severe and difficult to recover from. Inflammation and apoptosis may contribute to the heightened sensitivity of, and non-recovery from, AKI in patients with DKD. Resolvin D1 (RvD1) is a potent lipid mediator which can inhibit the inflammatory response and apoptosis in many diseases. However, it has been reported that the RvD1 levels were decreased in diabetes, which may explain why DKD is more susceptible to AKI. Methods For animal experiments, diabetic nephropathy (DN) mice were induced by streptozotocin (STZ) injection intraperitoneally. Renal ischemia–reperfusion was used to induce AKI. Blood urea nitrogen (BUN) and serum creatinine were determined using commercial kits to indicate renal function. Renal apoptosis was examined by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay. Real-time polymerase chain reaction (PCR) was used to detect the marker of inflammatory response. Western blot was used to detect the expression of nuclear factor-κB (NF-κB)-related proteins. For clinical study, 12 cases diagnosed with DKD were enrolled in this study, and an equal number of non-diabetic renal disease patients (NDKD) were recruited as a control group. The serum RvD1 in DKD or NDKD patients were detected through an ELISA kit. Results In clinical study, we found that the serum RvD1 levels were decreased in DKD patients compared to those in NDKD patients. Decreased serum RvD1 levels were responsible for the susceptibility to ischemic AKI in DKD patients. In animal experiments, both the serum RvD1 and renal ALX levels were downregulated. RvD1 treatment could ameliorate renal function and histological damage after ischemic injury in DN mice. RvD1 treatment also could inhibit the inflammatory response. Di-tert-butyl dicarbonate (BOC-2) treatment could deteriorate renal function and histological damage after ischemic injury in non-diabetic mice. RvD1 could inhibit the NF-κB activation and suppress inflammatory response mainly by inhibiting NF-κB signaling. Conclusion RvD1 attenuated susceptibility to ischemic AKI in diabetes by downregulating NF-κB signaling and inhibiting apoptosis. Downregulated serum RvD1 levels could be the crucial factor for susceptibility to ischemic AKI in diabetes.